Characterization of coastal ecosystems north of the managed resource protected area at the Guanahacabibes Peninsula, Cuba - Cobián, Dorka (2013)
The Guanahacabibes Peninsula was proposed as a Managed Resource Protected Area (APRM) in the Cuban National System of Protected Areas. In order to validate this proposal a study was conducted as part of the project “Implementation of a Regional Approach to the Management of Marine and Coastal Protected Areas in Southern Cuban Archipelagos”, with the purpose of characterizing coastal ecosystems and reassuring that the APRM designed location and extension correspond to the protection of the main natural resources of the region. Mangroves, coastal lagoons and seagrass were assessed as well as important sites for seabird and waterfowl communities and manatee populations. Sampling was conducted with methods validated in the project. Results included the baseline of the area and identified 149 algae species, 4 seagrass species, 53 mangrove fish species, and 39 seabird and waterfowl species. The sites selected as priority for habitat and species conservation and management include feeding and nesting sites for seabirds and waterfowl and two important sites for the manatee. The main problems for the area were identified for future conservation and management actions.